Influence of chloride on the anode dissolution of aisi 304 steel - Shtefan, V. V.; Kanunnikova, Nadiia; Balamut, Nataliia; Bofanova, Mariia (Sp. z o.o. "Diamond trading tour", 2018)
The kinetics of anodic dissolution of stainless steel in acidic sulphate-chloride solutions was studied. The regularities of changes in the electrochemical parameters (stationary potential, passivation potential, passivation current density, transpassivation potential) with varying concentration of NaCl are established.
Keywords: stainless steel; voltammetry; concentration; passivation